The Choice of Law Applicable to an International Arbitration Agreement – Application of the Lex Contractus Lying on its Deathbed? - Temonen, Matias (My University, 2023)
An arbitration agreement is a cornerstone of any arbitration. This thesis examines the choice of law applicable to the substantive validity of an international arbitration agreement, where the parties have not explicitly agreed on the applicable law. Pursuant to the doctrine of separability, the arbitration agreement is a separate and autonomous agreement from the underlying contract. Hence, the law applicable to the arbitration agreement must be determined independently as well. The law applicable to the underlying contract cannot be automatically extended to the arbitration agreement. The research examines the choice of law rules in private international law used to determine the law applicable to the substantive validity of the arbitration agreement. In a situation where the parties have not explicitly agreed on the law applicable to the arbitration agreement, either the law of the seat of arbitration, lex arbitri, or the law of the underlying contract, lex contractus, will become applicable either as the parties’ implicit choice of law or as the law with the closest connection to the arbitration agreement. The international legal state is unclear in this regard. In particular, there has been considerable confusion regarding the matter between civil law and common law jurisdictions. In international arbitration, it is likely that the arbitrators and the parties to the arbitration are domiciled in different legal cultures. Thus, this causes a significant problem. Thia paper critically examines, by means of pro et contra argumentation, the question of which law, lex arbitri or lex contractus, should apply to the arbitration agreement in the absence of the parties’ explicit choice of law. The aim is to understand the ratio decidendi of applying both possible laws and to outline the logical justification for applying one or the other. The main source material for the study is international case law and the views of leading scholars in the field, such as Alan Redfern, Gary Born, and Stefan Kröll. In order to harmonize internationally diverse and dramatically conflicting interpretations, the study suggests that the lex arbitri should take precedence over the lex contractus as the law applicable to the arbitration agreement. In the absence of the parties’ explicit choice of law, the parties’ agreement on the seat of arbitration should be taken to imply that the parties intended the lex arbitri to apply also to questions concerning the substantive validity of the arbitration agreement. This conclusion is further supported by the conflict of law rules of the New York Convention and the UNCITRAL Model Law, as well as by the fact that the lex arbitri has the closest and most real connection to the arbitration agreement. The practical value of arbitration as an alternative dispute resolution method is largely based on the requirements of procedural expediency, cost-efficiency, and predictability. Procedural disputes concerning the choice of law inside a substantive dispute are thus undesirable. Domestic arbitration acts and the arbitration rules of international arbitration institutes should impose provisions that lex arbitri applies to questions of the substantive validity of the arbitration agreement unless the parties have explicitly agreed otherwise. Costly and time-consuming choice of law disputes could be avoided if the choice of law rules were uniform at international level and the legal state were consistent.
Keywords: arbitration, choice of law, dispute resolution, doctrine of separability, lex arbitri